Response of steel pulse galvanostatic of embedded steel in alkali actived slag concrete (2015)
In this paper is presented the application of the galvanostatic pulse measurement which occurs in the activated slag concrete, submitted to accelerated carbonation processes. As reference material, we used ordinary Portland cement. Using the galvanostatic pulse technique enabled us the resistances values calculation which were involved separately in the carbonation process, allowing to find the corrosion rate by the Stern and Geary equation. The corrosion products were determined by the technique of Mössbauer Spectroscopy, corresponding to magnetite, goethite and wuestite.